Multinationals’ approach to the circular economy principles: an overview of the electronics sector and its sustainable efforts - Maria Sol Fernandes Marques Silva; Ana Paula Alves Cruz; Fabio Luiz Papaiz Gonçalves (Internext: Revista Eletrônica de Negócios Internacionais, 2025)
Objective: The aim of this study was to investigate how multinational companies (MNCs) are addressing sustainability issues in their operations and to what degree they adopt sustainable initiatives related to the circular economy (CE) principles.